2012
DOI: 10.1074/jbc.m112.361394
|View full text |Cite
|
Sign up to set email alerts
|

Redox-mediated Mechanisms Regulate DNA Binding Activity of the G-group of Basic Region Leucine Zipper (bZIP) Transcription Factors in Arabidopsis

Abstract: Background:The G-box cis-element is enriched in promoters of genes responding to light and to high light. Results: DTT induces DNA binding activity of bZIP transcription factors by reducing a disulfide bond. Conclusion: Redox regulation is crucial for DNA binding of the G-group of Arabidopsis bZIP transcription factors. Significance: Redox-dependent mechanisms modulate the activity of plant bZIPs in response to environmental signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 54 publications
2
85
0
Order By: Relevance
“…assays (EMSAs) revealed that purified bZIP16 recombinant protein could bind tandem repeats (43) of the G-box probe and form several mobility retarded protein-DNA complexes ( Figure 1B). This result confirms previous reports that the bZIP16-G-box complex could be formed by incubating the G-box probe with a crude protein mixture containing in vitro-translated bZIP16 protein or recombinant bZIP16 proteins Shaikhali et al, 2012). The formation of bZIP16-G-box complexes was reduced in the presence of excess unlabeled G-box competitors ( Figure 1B), which suggests that bZIP16 specifically binds to the G-box cis-element.…”
Section: Results Bzip16 Is a G-box Binding Proteinsupporting
confidence: 91%
See 1 more Smart Citation
“…assays (EMSAs) revealed that purified bZIP16 recombinant protein could bind tandem repeats (43) of the G-box probe and form several mobility retarded protein-DNA complexes ( Figure 1B). This result confirms previous reports that the bZIP16-G-box complex could be formed by incubating the G-box probe with a crude protein mixture containing in vitro-translated bZIP16 protein or recombinant bZIP16 proteins Shaikhali et al, 2012). The formation of bZIP16-G-box complexes was reduced in the presence of excess unlabeled G-box competitors ( Figure 1B), which suggests that bZIP16 specifically binds to the G-box cis-element.…”
Section: Results Bzip16 Is a G-box Binding Proteinsupporting
confidence: 91%
“…Therefore, bZIP16 might be a nuclear-localized transcriptional regulator. The nuclear localization of bZIP16 was previously observed by transient overexpression of bZIP16-fluorescent protein fusion proteins in either onion epidermal cells or Arabidopsis mesophyll protoplasts Shaikhali et al, 2012). To verify whether a biologically functional form of bZIP16 is indeed a nuclear protein, we introduced bZIP16-GFP (for green fluorescent protein) into the bzip16-1 mutant.…”
Section: Bzip16-green Fluorescent Protein Is a Nuclear Proteinmentioning
confidence: 95%
“…Fitting the observed curve of DNA-binding activity versus buffer redox potential to the Nernst equation for a two-electron reaction, a midpoint potential of 2238.4 6 1.4 mV at pH 7.5 was obtained. This potential is close to that of the GSH/ GSSG pair under these conditions (2269.6 mV; Veine et al, 1998;Bick et al, 2001) and fit in the range of 2170 to 2330 mV reported for several redox-regulated plant proteins such Rap2.4a, AtbZip16, ABI2, TRXs, and GRXs (Meinhard et al, 2002;Rouhier et al, 2008;Shaikhali et al, 2008Shaikhali et al, , 2012. It can be suggested that redox interconversions may operate under in vivo conditions to modulate the DNA-binding activity of TCP15.…”
Section: Cellular Redox Agents Modulate the Dna-binding Activity Of Tsupporting
confidence: 78%
“…The transcription factors regulated by ROS result in the transcription of a large number of genes (Maxwell et al, 2002;Miller et al, 2010;Smykowski et al, 2010;Shaikhali et al, 2012;Munné-Bosch et al, 2013). Recently, there has been a growing interest in understanding the regulation of senescence at the level of systems biology, using bioinformatics tools to build models for transcription factor networks (Penfold and Buchanan-Wollaston, 2014).…”
Section: Ros Generation and Scavenging: Spatiotemporal Effectsmentioning
confidence: 99%